Cloud-Based Accounting Systems : Solusi Transparansi Informasi Keuangan atau Hanya Ilusi Kecanggihan Teknologi ? - Widyadhana, Kun Aulia; Kirana DP, Rina Tjandra (FEB Universitas Maritim Semarang, 2025)
Cloud-Based Accounting Systems (CBAS) are technological innovations that support digital transformation in financial management by increasing efficiency, transparency, and real-time data access. This system helps companies reduce manual recording errors, improve reporting accuracy, and accelerate data-based decision-making processes. In addition, CBAS also has advantages in terms of flexibility of use and compliance with accounting standards, making it a relevant solution for modern companies. Although CBAS offers many benefits, its implementation can also create a perception of technological superiority that does not fully reflect reality if it is not balanced with organizational and human resource readiness. Challenges often faced in implementing CBAS include dependence on cloud services, data security threats, and errors in system input or configuration that can lead to inaccurate financial reports. In addition, overly high expectations for automation can lead to neglect of manual supervision that is still needed to maintain the reliability of financial information. The success of CBAS implementation is highly dependent on a well-designed implementation strategy, adequate user training, and appropriate risk mitigation measures. With careful planning and a strategic approach, CBAS can serve as a tool that increases financial transparency and efficiency, not just a technology trend that provides no real benefits.